Bat fauna from the Sooretama Biological Reserve, southeastern Brazil (Acta Scientiarum. Biological Sciences, 2024)
The Atlantic Forest is one of the world's hotspots of biodiversity, a heterogeneous biome encompassing tropical and subtropical vegetation formations. Its remnants in the state of Espírito Santo, southeastern Brazil, are mostly within state and federal Conservation Units. The largest Unit is the Sooretama Biological Reserve, which harbors several endemic occurrences of fauna and flora, and is the last refuge of some threatened animal species. Inventories of fauna are essential to know the community composition, and for the elaboration of preservation strategies. We conducted a survey focused on the bat fauna of the Sooretama Reserve, analyzing the trophic guilds and the conservation status of its species. We surveyed online taxonomic databases and the literature, resulting in 402 records from two different scientific collections. These records represent five families, 39 genera, and 57 species of bats, revealing that the Sooretama Biological Reserve has all known bat families in the Atlantic Forest biome. Phyllostomidae was the family with the highest number of species registered, and a majority of species belongs to the aerial insectivorous trophic guild. Four species are registered as “Vulnerable” in state and federal conservation books.